Influence of groundwater inflow on water temperature simulations of Lake Ammersee using a one-dimensional hydrodynamic lake model - Bueche, Thomas; Vetter, Mark (ERDKUNDE, 2014)
In this study we implemented groundwater inflow to the one-dimensional hydrodynamic simulation of lake water temperatures to improve the reproduction of the real water temperatures by the simulation results for Lake Ammersee, Southern Germany. As the hydro-geological conditions at Lake Ammersee have not yet been finally clarified, we created simulation scenarios for the hydrodynamic modeling with various characteristics of sub-terrestrial inflow. The scenarios were based on a review of the state of available information regarding the geology of the Ammersee basin. Analysis of the simulation results for each scenario revealed obvious alterations in the reproduction of real-temperature in comparison to those produced without accounting for subsurface inflows. For some inflow characteristics the implementation of groundwater inflow induced more accurate approximations of simulation results to real conditions for almost all depths and seasons. This implies that the hydrodynamic simulation of water temperatures at Lake Ammersee, including subsurface inflow, provides reliable results. Additionally it was possible to estimate roughly the potential conditions of groundwater inflow into the lake.